MANAGEMENT OF TRINEXAPAC-ETHYL APPLICATION IN SOYBEAN (Nativa, 2023)
This work aimed to evaluate the effects of using the management of growth regulator trinexapac-ethyl (Moddus®)) over plant height, lodging, productivity and grain yield of soybean plants (Glycine max (L.) Merrill. cv. BS 2606 IPRO). For that, an experiment was installed in field conditions, by using a randomized block design, with four replications; the experimental unit was constituted of five lines four meters in length, spaced at 0.45 m.  Treatments were constituted by the application of growth regulator, as follows: without application; total dose between V3 and V4; total dose between V5 and V6; ½ dose between V3 and V4 + ½ dose between V5 and V6; total dose between V3 and V4 + total dose between V5 and V6, totaling five treatments. Productive components, mass of 100 grains and grain yield were evaluated. Results were insignificant for studied variables regardless of management, differing only from the control.Keywords: oilseed; lodging; plant regulator; application management; grain yield. Manejo da aplicação de trinexapac-ethyl na soja RESUMO: Esse trabalho teve por objetivo avaliar os efeitos da utilização de manejos do regulador de crescimento (trinexapac-ethyl (Moddus®)) sobre altura, acamamento, produtividade e rendimento de plantas de soja (Glycine max (L.) Merrill. cv. BS 2606 IPRO). Com isso, instalou-se um experimento em condições de campo, com o delineamento experimental de blocos casualizados, com quatro repetições; a unidade experimental constituiu-se de cinco linhas de quatro metros de comprimento, espaçadas em 0,45 m entre elas. Os tratamentos foram constituídos pela aplicação do regulador de crescimento, sendo: sem aplicação; dose total entre V3 e V4; dose total entre V5 e V6; ½ dose entre V3 e V4 + ½ dose entre V5 e V6; dose total entre V3 e V4 + dose total entre V5 e V6, perfazendo cinco tratamentos. Foram avaliados os componentes produtivos, massa de 100 grãos e produtividade. Os resultados não foram estatisticamente significativos para as variáveis avaliadas independente dos manejos, diferindo apenas da testemunha.Palavras-chave: oleaginosa; acamamento; regulador vegetal; manejo de aplicação; produtividade.